"Stonewall Jackson" : the life and military career of Thomas Jonathan Jackson - Addey, Markinfield (Online access with subscription: Proquest Ebook Central., 2001)
"Stonewall" Jackson has been considered by military authorities to be one of the most brilliant commanders of his time. He had a skillful, though sometimes peculiar, style of fighting that could turn the tide of a battle in the Confederate favor and avoid disastrous defeat.